2019
DOI: 10.1111/jnc.14685
|View full text |Cite
|
Sign up to set email alerts
|

GM1 promotes TrkA‐mediated neuroblastoma cell differentiation by occupying a plasma membrane domain different from TrkA

Abstract: Recently, we highlighted that the ganglioside GM1 promotes neuroblastoma cells differentiation by activating the TrkA receptor through the formation of a TrkA–GM1 oligosaccharide complex at the cell surface. To study the TrkA–GM1 interaction, we synthesized two radioactive GM1 derivatives presenting a photoactivable nitrophenylazide group at the end of lipid moiety, 1 or at position 6 of external galactose, 2; and a radioactive oligosaccharide portion of GM1 carrying the nitrophenylazide group at position 1 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 66 publications
(186 reference statements)
2
58
0
1
Order By: Relevance
“…Subsequently, N2a cells were incubated with the basolateral solution containing the hBLEC-crossed OligoGM1. As shown in Figure 9a, hBLEC-crossed OligoGM1 induced a neuron-like morphology after 24 h. In accordance with the OligoGM1 behavior reported in previous studies [22,23], the N2a receiving hBLEC-crossed OligoGM1 showed a clear neurite sprouting that was instead absent in the round-shaped control cells.…”
Section: Maintenance Of Neurotrophic Properties For Hblec-crossed Olisupporting
confidence: 90%
See 4 more Smart Citations
“…Subsequently, N2a cells were incubated with the basolateral solution containing the hBLEC-crossed OligoGM1. As shown in Figure 9a, hBLEC-crossed OligoGM1 induced a neuron-like morphology after 24 h. In accordance with the OligoGM1 behavior reported in previous studies [22,23], the N2a receiving hBLEC-crossed OligoGM1 showed a clear neurite sprouting that was instead absent in the round-shaped control cells.…”
Section: Maintenance Of Neurotrophic Properties For Hblec-crossed Olisupporting
confidence: 90%
“…Additionally, we previously reported that OligoGM1 induces N2a neuritogenesis by eliciting the activation of the TrkA-ERK1/2 pathway [22,23]. Importantly here, by immunoblotting, we highlighted the activation of the TrkA-ERK1/2 pathway by hBLEC-crossed OligoGM1, as shown in Figure 9b.…”
Section: Maintenance Of Neurotrophic Properties For Hblec-crossed Olisupporting
confidence: 71%
See 3 more Smart Citations